Estimates of Intrinsic Square Functions on Generalized Weighted Morrey Spaces - Guilian Gao; Xiaomei Wu (Journal of Function Spaces)
We prove the boundedness of the intrinsic functions on generalized weighted Morrey spaces Mp,φ(w), including the strong type estimates and weak type estimates. Moreover, we define the kth-order commutators generated by BMORn functions and intrinsic functions, and obtain their strong type estimates on Mp,φ(w). In some cases, we improve previous results.